CLINICOPATHOLOGIC AND IMMUNOHISTOCHEMICAL CHARACTERIZATION OF LOCALIZED JUVENILE SPONGIOTIC GINGIVAL HYPERPLASIA - DE MENDOZA, IRENE LAFUENTE IBAÑEZ; ZAPATA, JUAN PABLO MUÑOZ; HERRERA, FERNANDO GARCÍA; MENESES, JUAN CARLOS COCA; NAVARRO, JAVIER ALBERDI; URIZAR, JOSÉ MANUEL AGUIRRE (Oral surgery, oral medicine, oral pathology and oral radiology, 2020)
Localized juvenile spongiotic gingival hyperplasia (LJSGH) is a clinicopathologic entity that affects young patients, which often involves the anterior gingiva of the upper maxillary. Its origin is controversial, and neither infectious nor hormonal factors have been recognized. Clinically, it appears as an irregular papillary and reddish mass. We present a series of 10 cases, 5 women and 5 men, whose mean age was 13 years. We analyze their main clinical and histologic characteristics, as well as their immunochemical profile (CK14, CK17, CK19, CD3, CD20, S-100, VEGFα, and ki-67), with the aim of explaining its origin and possible etiopathogenesis. Based on obtained data, the results show that LJSGH is not an epuliform lesion of a reactive nature, but a specific clinicopathologic entity, strongly related to persistency of the junctional epithelium. This research was supported by a Research Group from UPV/EHU (PPG17/01).